'Wage', 'Salary' and 'Remuneration': A Genealogical Exploration of Juridical Terms and their Significance for the Employer's Power to Make Deductions from Wages. (30th April 2018) - Adams, Zoe
Abstract: The Supreme Court in Hartley v King Edwards VI College (2017) has confirmed that an employee who refuses to work in accordance with his contract forfeits his right to be paid for the duration of the breach. The decision extends to professional employees paid a periodical salary the principle established in Miles v Wakefield MDC (1987). The present article sheds new light on these decisions by situating them within a broader debate concerning the function of the wage and the proper relationship between work and payment. Drawing on insights from economic theory, and engaging in a genealogical analysis of legal concepts, the article shows how this debate has, over time, conditioned the use of concepts such as the 'wage', 'the salary' and 'remuneration' in legislation and case law concerning deductions. It shows that the legal concept of the 'wage' is closely related to the economic idea of the wage as the price of a commodity, while the legal concepts of 'salary' and 'remuneration' are more closely analogous to the economic idea of the wage as the cost of subsistence. The courts' tendency to confuse these concepts, and to analyse the employer's power to deduct as a right to withhold wages for non-performance of the contract, tells us much about the implicit assumptions underpinning cases, such as Miles and Hartley, and how they have shaped the path of the law.